HUBUNGAN GAYA KEPEMIMPINAN DENGAN KOMITMEN ORGANISASI KARYAWAN PABRIK (Kasus Bagian Pulp Making 9 PT. Indah Kiat Perawang) - Febrina Yutri Aviesha; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The issue of the application of leadership style is a major problem in determining the success of the company. To the PT. Indah Kiat section Pulp Making 9 Perawang is a private company engaged in the production of paper, if notice of the company is likely to use the leadership style of telling. The problem in this company as a result of labour turn over in particular, which resulted in losses to the company. Employees are one of the most important factors of production in the company. Without employees, the company would be difficult to achieve the goals that have been set.One phenomenon that describes the organizations lack of commitment by employees of the Pulp Making 9 PT. Indah Kiat Perawang is can be seen from labour turn over (LTO).The results of the study can be concluded as follow: Application of leadership style that includes the indicators telling, selling, participating, delegating to the PT. Indah Kiat section Pulp Making 9 categorized agree, this indicates that the style of leadership in the company can be received by the employee with either.In connection with the organizational commitment of employees to the leadership style treatment of employees with good leadership it will certainly lead to better the commitment of subordinates, however the statement of four indicators leadership style used in this study turned out to respondents is inconsistent, still there are respondents who disagree and neutral.For the implementation of the leadership style to the PT. Indah Kiat section Pulp Making 9 more appropriate to use the leadership style of selling.For employee commitment to the organization is basically good or approved, just still a lot that needs to be improved in order to reduce labour turn over in employees. While the relationship of leadership style and organizational commitment of employees is basically strong with reason when leadership style performed by using force selling.Keywords : leadership style , organizational commitment , telling , selling